Formulation of a Culture Medium to Optimize the Production of Lipopeptide Biosurfactant by a New Isolate of Bacillus sp.: A Soil Heavy Metal Mitigation Approach - Kalvandi, Sahar; Garousin, Hamidreza; Pourbabaee, Ahmad Ali; Alikhani, Hossein Ali (Frontiers in Microbiology, 2022)
This research aimed to optimize a lipopeptide biosurfactant produced from Bacillus sp. SHA302 due to its high efficiency of heavy metal release in soil. The results demonstrated that the metal release capacity of the lipopeptide biosurfactant alone increased with increasing the biosurfactant concentration. Among treatments with different biosurfactant concentrations plus acid, the highest metal release rates of 53.8% ± 1.4 and 39.3% ± 1.7 for Zn and Pb, respectively, were observed in the critical micelle concentration (CMC) + HCl treatment. The results of a factorial experiment designed for optimizing biosurfactant production showed that among five inexpensive carbon sources and six mineral nitrogen sources, sugar beet molasses (1%) and ammonium chloride (0.1%) were the most efficient sources in lowering the surface tension (ST) of the culture media to 32.2 ± 0.76 mN/m. The second step of the experiment was a Plackett–Burman design with 11 factors and showed that the four factors of pH, ammonium chloride, magnesium sulfate, and molasses significantly affected (P < 0.05) the changes in ST and biosurfactant production. The third step of the experiment was done using the response surface methodology (RSM) with a central composite design. The results showed that a pH of 7.3, 1.5 g/l of ammonium chloride, 0.3 g/l of magnesium sulfate, and 10% of sugar beet molasses yielded values of 29.2 ± 0.71 mN/m and 5.74 ± 0.52 g/l for the two variables of ST and biosurfactant production, respectively, which reached their most optimal levels.